MEDIA GAMBAR SEBAGAI INOVASI PEMBELAJARAN IPS : MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA MI - Nailil Rohmawati; Imaniar Mahmuda (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Social Science material is often considered difficult and boring by students due to the abstract nature of the presentation and the lack of innovative instructional media. This research focuses on improving student interest and learning outcomes through the implementation of image media as a concrete solution. Using a Classroom Action Research design implemented in two systematic cycles, this study involved eighteen fourth-grade students at MI Nurul Islam Selok Awar-Awar. The research stages included action planning, classroom intervention, participatory observation, and ongoing reflection. The research findings showed significant improvements in each cycle. Quantitatively, classical mastery increased from 56 percent in the first cycle to 78 percent in the second cycle, with an average score increasing from 66.16 to 78.32. The effectiveness analysis showed an N-Gain value of 0.359, which is in the moderate category, while learning interest jumped drastically from 56 percent to 89 percent. The main conclusion confirms that the use of image media as a learning innovation has proven to be very effective in visualizing abstract concepts, encouraging active involvement, and optimizing student academic achievement. These results provide a practical contribution for educators to transform the classroom atmosphere to be more dynamic and meaningful in order to support the success of social studies learning at the madrasah level in a sustainable manner through the integration of visual elements that are on target and educational for the overall growth of students in elementary schools.